Population-based study of DNA image cytometry as screening method for esophageal cancer - Zhao, Lin (World journal of gastroenterology : WJG, 2012)
AIM：To explore the DNA image cytometry （DNA-ICM） technique as a primary screening method for esopha-geal squamous precancerous lesions.METHODS：This study was designed as a population-based screening study.A total of 582 local residents aged 40 years-69 years were recruited from Linzhou in Henan and Feicheng in Shandong.However,only 452 subjects had results of liquid-based cytology,DNA-ICM and pathology.The sensitivity and specificity of DNA-ICM were calculated and compared with liquid-based cytology in moderate dysplasia or worse.RESULTS：Sensitivities of DNA-ICM ranging from at least 1 to 4 aneuploid cells were 90.91%,86.36%,79.55% and 77.27%,respectively,which were better than that of liquid-based cytology （75%）.Specifici-ties of DNA-ICM were 70.83%,84.07%,92.65% and 96.81%,but the specificity of liquid-based cytology was 91.91%.The sensitivity and specificity of a combination of liquid-based cytology and DNA-ICM were 84.09% and 85.78%,respectively.CONCLUSION：It is possible to use DNA-ICM tech-nique as a primary screening method for esophageal squamous precancerous lesions.